Crash : Sebuah Kajian tentang Kemarahan - Febby Pratama Putra; Laila Desnaranti (Neolectura, 2023)
The objective of this study is to examine the anger in Paul Haggis's film Crash. The author of this study identifies the sources and manifestations of anger in the film Crash. The author employs a descriptive qualitative approach. In order to evaluate the data, and explain anger, and the reasons and styles of anger, the writer uses a number of theories that have been put forth by the experts as a foundation. According to the writer,